THE DETERMINANTS OF JOB SATISFACTION IN PUBLIC SERVICE ORGANIZATION - Muhammad Ashraf; Nawaz Ahmad; Omer Ahmed Shaikh; Saleem Raza Bhatti; Abdul Hakeem Soomro (European Scientific Journal, ESJ, 2013)
The aim of this study is to identify the impact of demographic, working environment and managerial control determinants on job satisfaction. Job satisfaction has been a major course of study long time ago. However, in Pakistani context, little focus has been made on job satisfaction of public service employees. Pakistan is country whereby working in public service organization is deemed attractive. The organizational objective behind public owned sectors is to serve the community; hence identifying the determinants of job satisfaction of public sector officials has been the major focus of this study. Data was obtained from the employees of Karachi Water Sewerage Board through structured questionnaire. Hence, beside secondary sources of data, this paper mainly depends upon primary source of data. The study find out that 95% of variance is explained by demographic, working environment and managerial control for the level of job satisfaction among employees of Karachi Water & Sewerage Board.